Karakteristik Maseral dan Peringkat Batubara Daerah Balikpapan Selatan Berdasarkan Analisis Petrografi Organik - ., Jamaluddin; Pratikno, Fathony Akbar; Taslim, A. Ibnu; Kaunang, Imanuel (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2025)
This study aims to characterize the maceral composition and determine the rank of coal from the Kampungbaru Formation in the South Balikpapan area based on organic petrography analysis. Coal samples were analyzed using reflectance microscopy to identify and quantify maceral components and measure vitrinite reflectance. The analysis results indicate that the huminite maceral group dominates the coal composition (60.7-84.6%), followed by liptinite (9.8-27.5%), and low inertinite (5.6-11.8%). Vitrinite reflectance ranges from 0.30-0.33%, indicating that the coal is in the lignite to sub-bituminous rank. This low coal rank reflects rapid deposition conditions and an anoxic to suboxic environment that inhibits the complete decomposition of organic matter.